FACTORS FOR CORPORATE MANAGEMENT IMPROVEMENT AT ENTERPRISES IN COMPETITIVE CONDITIONS - Polianska , A.S. (The actual problems of regional economy development, 2018)
The article considers the urgency, preconditions and directions of improvement of corporate management in domestic practice. General peculiarities of such activity in Ukrainian practice are summarized. The expediency of a competitive approach applying to improve the corporate governance by substantiating the efficiency of the corporate sector of the economy and encouraging investors to invest in the real sector of the national economy is substantiated. Attention is drawn to the fact that corporate governance improving on the basis of a competitive approach allows us to take into account both the factors of the external environment formed by successful corporations and creating the competitive advantages on the international level, and the internal environment, which forms a stable competitive advantages of each corporation in accordance with the operating system of management in the organization. The key ways of improving corporate governance for domestic enterprises are summarized and groups of factors that have an impact on the management of corporations are highlighted.